Intestinal autoflora of the test subjects in a 6-month biological engineering experiment - Rerberg, M S; Manukovskiĭ, N S; Somova, L A (Kosmicheskaia biologiia i aviakosmicheskaia meditsina, 1977)
During a 6-month bioengineering experiment the intestinal microflora of four test subjects was examined. Changes in the composition of different groups of intestinal microflora (bifidobacteria, lactic-acid bacteria, sporogenous anaerobes, proteus, etc) were found. In spite of the unstable pattern of the intestinal microflora and its tendency for simplification, the total number of microorganisms in 1 g of feces remained relatively unchanged in all the test subjects.